Russian Federation : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
The reports highlights that, even though the Russian economy has started reviving from the crisis, growth has been moderate and inflation high. Executive Directors have advised that the focus should be on reducing fiscal vulnerabilities, lowering inflation, promoting a stronger and more competitive banking system, and creating a favorable environment for investment and economic diversification. Directors encouraged the authorities to undertake growth-friendly, credible, and ambitious fiscal consolidation. They have supported the Financial Sector Assessment Program (FSAP) recommendations to strengthen financial sector policies.